Entrepreneurial self-efficacy as a key driver of students' entrepreneurial interest: the roles of entrepreneurship education, family support, and access to capital - Kalista Kalista; Suhardi Suhardi; Nur Hidayati (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the influence of entrepreneurship education, family support, and access to capital on students' entrepreneurial interest with entrepreneurial self-efficacy as a mediating variable. The study used a quantitative approach with an explanatory research design. Data were collected through questionnaires distributed to students and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4. The results showed that entrepreneurship education, family support, and access to capital had a positive and significant effect on entrepreneurial self-efficacy. In addition, entrepreneurial self-efficacy, entrepreneurship education, and family support also had a positive and significant effect on entrepreneurial interest, while access to capital did not have a significant direct effect. The results of the mediation analysis showed that entrepreneurial self-efficacy was unable to significantly mediate the relationship between the independent variables and entrepreneurial interest. This study confirms that psychological and social factors are more dominant than financial factors in shaping students' entrepreneurial interest.